Caveat Venditor: Trust Asymmetries in Acquisitions of Entrepreneurial Firms - Graebner, Melissa E. (Academy of Management Journal, 2009)
I explore the role of trust in acquisitions of entrepreneurial firms, taking a dyadic view that gives equal attention to buyers and sellers. The two parties have asymmetric views regarding whether their counterparts are trustworthy. I outline how these asymmetries emerge, persist, and influence behavior, including tendencies to behave deceptively and to guard against deception. I also find that buyers' and sellers' beliefs concerning whether their counterparts are trustworthy and trusting are often erroneous. I explore the implications of these findings for developing a theory of trust asymmetries and argue that selecting buyers on the basis of trust increases rather than diminishes entrepreneurs' vulnerability.